DAMPAK MEDIA SOSIAL FACEBOOK TERHADAP JUAL BELI SAPI DI PETERNAKAN NUR NAJWA KELURAHAN PANRENG KABUPATEN SIDENRENG RAPPANG - Armitha Putri Ramadhani; Haslindah; Adam Latif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the impact of using Facebook on cattle trading at Nur Najwa Livestock, Sidenreng Rappang Regency. The primary problem addressed is the challenges faced by farmers in digital marketing and the need to understand the effectiveness of social media in increasing transactions. The purpose of this study is to analyze the influence of Facebook usage on cattle buying and selling activities and to identify the influencing factors. The research method employed is a quantitative approach with correlational research design through a survey of 94 respondents. Data were collected via observations, questionnaires, and interviews, then analyzed using simple linear regression with SPSS software. The results indicate that Facebook usage has a positive and significant effect on trading activities with a t-statistic of 23.054. The coefficient of determination (R²) of 0.852 shows that Facebook contributes 85.2% to the success of transactions, including sales volume, price, and profit. In conclusion, digital transformation through Facebook effectively expands market reach and significantly increases livestock farm income.